2009
DOI: 10.1002/jmri.21666
|View full text |Cite
|
Sign up to set email alerts
|

Spleen R2 and R2* in iron‐overloaded patients with sickle cell disease and thalassemia major

Abstract: Purpose: To evaluate the magnetic properties of the spleen in chronically transfused, iron-overloaded patients with sickle cell disease (SCD) and thalassemia major (TM) and to compare splenic iron burdens to those in the liver, heart, pancreas, and kidneys. Results:The spleen showed a different R2-R2* relationship than that previously established for the liver. At high iron concentrations (R2* Ͼ 300 Hz), spleen R2 was lower than predicted for liver. The proportion of splenic to hepatic iron content was greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 45 publications
(67 reference statements)
3
63
1
Order By: Relevance
“…With regard to splenic iron quantification, there was a common assumption in human studies that SIC quantification could be derived from the LIC quantification formula (18,19). In contrast, our study showed significant differences between the estimation formulas of LIC and SIC, whatever the chosen MRI parameter.…”
Section: Discussioncontrasting
confidence: 68%
“…With regard to splenic iron quantification, there was a common assumption in human studies that SIC quantification could be derived from the LIC quantification formula (18,19). In contrast, our study showed significant differences between the estimation formulas of LIC and SIC, whatever the chosen MRI parameter.…”
Section: Discussioncontrasting
confidence: 68%
“…Further, the significantly longer duration of exposure to transfusion and chelation in splenectomized patients would also be explained by the older age of these patients rather than their contribution to cardiac iron content as the duration of transfusion and chelation did not differ significantly in patients with cardiac iron loading compared with noncardiac iron loading patients. In line with the observation of Brewer et al, 12 it could be speculated that removing the iron-buffering capacity of the spleen by splenectomy may contribute to myocardial iron loading.…”
Section: Discussionmentioning
confidence: 67%
“…A relationship between pancreatic and cardiac R2* was predictable given that both organs take up NTBI. 8 The relatively high linear correlation in TM patients suggests a graded response in both tissues and has been reported by us 14 and by others. 4 In the present study, the relationship was maintained across multiple time points (an average of 2 studies per patient).…”
Section: Discussionmentioning
confidence: 84%